Contested mining, state selectivities, and the reform of the mining law in Mexico - Hernández Westpfahl, Rafael; Lehmann, Rosa (Political geography, 2025)
Research on extractivism has dealt with state policy struggles and the role of progressive governments in Latin America since the 2000s, with particular attention on the integration of formerly marginalized or opposing interests into government strategies and policies. Building on materialist state theory, we argue that a closer focus on selectivities of the state can better explain both the shifts towards an integration of formerly excluded demands and continuities in state selectivities favoring established accumulation strategies. We illustrate our argument through an analysis of the reform to Mexico's mining law. Backed by large sectors of society, representatives of the leftist government partly incorporated longstanding critique of large-scale mining into new or revised regulations. We view this reform as a magnifying glass that helps us examine changing power relations, showing how demands from actors that previously had little access to the state arena have been negotiated and how this shifted state selectivities in favor of anti-mining claims. By examining changes in Mexico's mining legislation, our study adds to the growing body of scholarship that analyzes the role of the state and left-wing governments in contested resource extraction from a historical-materialist perspective. Our contribution is both empirical and theoretical. Empirically, it examines the changing role of the state in extractivism within a country and geopolitical setting different from those studied in research on neo-extractivism in the 2000s. On the theoretical level, our analysis of a law and its reform uncovers power relations and struggles related to mining, as well as existing and shifting state selectivities. Our analysis thus informs theory-led empirical research on similar struggles over state involvement and regulation in other Latin American countries, particularly in the context of changing geopolitics and increasing demand for minerals and metals.